2007
DOI: 10.1128/aem.01059-07
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Closely Related but Phenotypically Divergent Trichoderma Species Cause Green Mold Disease in Oyster Mushroom Farms Worldwide

Abstract: The worldwide commercial production of the oyster mushroom Pleurotus ostreatus is currently threatened by massive attacks of green mold disease. Using an integrated approach to species recognition comprising analyses of morphological and physiological characters and application of the genealogical concordance of multiple phylogenetic markers (internal transcribed spacer 1 [ITS1] and ITS2 sequences; partial sequences of tef1 and chi18-5), we determined that the causal agents of this disease were two genetically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
113
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 118 publications
(129 citation statements)
references
References 28 publications
8
113
0
1
Order By: Relevance
“…All the 20 isolates collected from the button mushroom compost were identifi ed as T. harzianum, while strains isolated from the oyster mushroom substrate included T. pleurotum and T. pleuroticola (9 and 11 isolates, respectively). Alignments (20) revealed that the ITS sequences of the isolates belonging to the same species did not share the same pattern. The differences suggested that they belonged to different strains within the species, but this did not affect the results of identifi cation.…”
Section: Species Identifi Cationmentioning
confidence: 99%
See 2 more Smart Citations
“…All the 20 isolates collected from the button mushroom compost were identifi ed as T. harzianum, while strains isolated from the oyster mushroom substrate included T. pleurotum and T. pleuroticola (9 and 11 isolates, respectively). Alignments (20) revealed that the ITS sequences of the isolates belonging to the same species did not share the same pattern. The differences suggested that they belonged to different strains within the species, but this did not affect the results of identifi cation.…”
Section: Species Identifi Cationmentioning
confidence: 99%
“…Recently, green mould disease of cultivated oyster mushroom has also been reported in several countries (12)(13)(14)(15)(16)(17)(18), and the causal agents were identifi ed and described as new species T. pleurotum and T. pleuroticola (19,20).…”
Section: Pleurotus Ostreatusmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that the highest assimilation rates for T. pleuroticola occurred on N-acetyl-D-glucosamine and quinic acid, which could be useful for differentiation of two causative agents of Pleurotus green mold disease. T. pleuroticola, on the other hand, can be distinguished from T. aggressivum (green mold disease on Agaricus) by the inability of the latter to utilize α-ketoglutaric, L-malic, and succinamic acids (Komon-Zelazowska et al, 2007). Thus, these kinds of assays are important sources of complementary data for precise species identification and as a starting point for uncovering the ecological niche of a fungus.…”
Section: Intra-and Inter-specific Variability In Carbon Source Utilizmentioning
confidence: 99%
“…Moreover, PMs could also differentiate subpopulations within Dendryphiella species in relation to their geographic origin (dela Cruz et al, 2006). Nutrient source profiling was also applied by Komon-Zelazowska et al (2007) to determine the evolutionary context of two genetically closely related, but phenotypically very different species (Trichoderma pleuroticola and T. pleurotum) that cause green mold disease in oyster mushroom (Pleurotus ostreatus) farms worldwide. This assay revealed generally impaired growth of T. pleurotum on numerous carbon sources according to enhanced assimilation of those by T. pleuroticola, which thereby showed very similar metabolic characteristics to its phylogenetically close members in the Harzianum clade of Hypocrea/Trichoderma (T. harzianum and T. aggressivum).…”
Section: Intra-and Inter-specific Variability In Carbon Source Utilizmentioning
confidence: 99%